Emailed implementation supports to promote treatment integrity: Comparing the effectiveness and acceptability of prompts and performance feedback. (June 2018) - Fallon, Lindsay M.; Collier-Meek, Melissa A.; Kurtz, Kathryn D.; DeFouw, Emily R.
Abstract: Teachers struggle to maintain high levels of treatment integrity, which are associated with efficient improvements in student outcomes. To address this challenge, school psychologists can provide implementation support, such as prompts or performance feedback, to increase teachers' treatment integrity when it is low. Implementation prompts are an emerging implementation support having been investigated in one previous study, but are feasible and require little time to provide. Performance feedback is an evidence-based practice, but requires more time for school psychologists to coordinate and deliver. The current study sought to compare the emailed delivery of prompts and performance feedback directly. Three elementary school teachers from a diverse setting participated with their students in this experimental multiple baseline single-case design research study. Teachers were trained to implement a classwide group contingency intervention and, when treatment integrity was low, received prompts and then performance feedback. Direct observation of treatment integrity and classwide behavior indicated that performance feedback was slightly more effective at increasing treatment integrity, but implementation prompts were modestly effective, took less time to provide, and were viewed as more acceptable by teachers. Furthermore, student outcomes (academic engagement and disruptive behavior) were relatively stable across the emailed prompts and performance feedback phases, suggesting the supports were similarly effective. Future research might further investigate these findings and continue to build the research base for implementation supports to promote treatment integrity.